PEMBUBARAN LEMBAGA NEGARA NON STRUKTURAL DALAM PERATURAN PRESIDEN NO.112 TAHUN 2020 PERSPEKTIF RESTRUKTURISASI BIROKRASI - Putri Alvanita (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
Abstract: Based on Presidential Regulation No. 112 of 2020, there were 10 non-structural state institutions that were disbanded with the aim of increasing the effectiveness and efficiency of implementing government affairs and national development strategies, so it is interesting to examine from the perspective of Bureaucratic Restructuring because this theory includes institutional structural reforms. The research method used in this research is qualitative research using a normative juridical approach, namely conducting research using literature or research on legal principles. From the results of this study, it is stated that (1) The main reason for the dissolution of non-structural state institutions according to Presidential Regulation No. 112 of 2020 is an effort to increase the effectiveness and efficiency of the implementation of government work, to achieve development strategy plans and the bureaucracy which is considered too full, (2 ) The position of Non-Structural State Institutions in the constitutional system of the Republic of Indonesia is directly under the leadership of the President of the Republic of Indonesia, (3) The dissolution of Non-Structural State Institutions based on Presidential Regulation No. 112 of 2020 in accordance with the Theory of Bureaucratic Restructuring because it is in line with the form of Bureaucratic Restructuring, namely: Downsizing, Delayering, Decentralizing, Reorganization, Cost Reduction Strategy, and Competency. Where the theory of bureaucratic restructuring in the government system in Indonesia is currently seen as very important to realize a government system that is in accordance with the goals of the Indonesian state.